Political interests in the creation process of the Metropolitan Region of Umuarama, State of Paraná - Oliveira, Renato Alves de; Borges, William Antonio (Pontifícia Universidade Católica de São Paulo, 2021)
In this article, we sought to understand the political interests inscribed in the process of creating the Metropolitan Region of Umuarama (MRU). For that, the research mobilized the current legislation, the Metropolis Statute, which is the legal basis for the metropolitan dynamics and establishes criteria for the institution of new MRs. The theoretical approach covered the literature on the metropolitan issue in Brazil and on the public policy process. The methodology involved documentary research and field research carried out through semi-structured interviews. As a result, the constructed narrative tells us that the decision to create the MRU was based on political interests connected with the status of belonging to a MR, on real estate interests and on electoral interests.